A probiotic hygiene product and preparation method thereof

By using materials such as sodium alginate and polyvinyl alcohol to form probiotic embedded particles and load them on the polyethersulfone nanofiber membrane, the problems of low retention of probiotic activity and poor use stability are solved, and the efficient survival and stability of probiotics are achieved.

CN119345439BActive Publication Date: 2025-04-04福建省福地新材料股份有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411926680.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The activity retention rate of probiotics in existing probiotic sanitary products is low and the stability of use is poor, which can easily lead to inactivation and shedding of probiotics.

Method used

Sodium alginate and polyvinyl alcohol are used as shell solution, and the bacterial solution containing probiotics are mixed with polyvinyl alcohol solution as core layer solution. Soy protein isolate and calcium chloride are used as receiving solution to form probiotic-embedded particles through coaxial electrostatic spraying, and they are loaded on the polyethersulfone nanofiber membrane. Probiotic-rich fibers are formed by spraying pectin solution and composite spinning technology.

Benefits of technology

It improves the heat resistance and storage stability of probiotics, enhances the survival rate and use stability of probiotics, and makes the probiotic hygiene products made more soft, comfortable, skin-friendly and breathable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of sanitary products, and specifically discloses a probiotic sanitary product and a preparation method thereof. A probiotic sanitary product comprises a probiotic non-woven fabric, the probiotic non-woven fabric contains probiotic-rich fibers, and the preparation method of the probiotic-rich fibers is as follows: dissolving soy protein isolate and calcium chloride to obtain a receiving solution; coaxially electrostatically spraying the shell solution and the core solution to obtain probiotic-embedded particles; electrostatically spinning polyethersulfone to obtain a polyethersulfone nanofiber membrane; adding the probiotic-embedded particles to a pectin solution to obtain a spraying liquid, spraying the spraying liquid on the polyethersulfone nanofiber membrane to obtain a blended powder; mixing the blended powder with a PE resin and an auxiliary agent in a mass ratio, extruding, and granulating to obtain a shell material, and composite spinning the shell material and PET slices. The probiotic sanitary product of the present application has the advantages of high probiotic survival rate, good storage stability, high activity retention rate, high water holding capacity, and good antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sanitary products, and more specifically, to a probiotic sanitary product and a preparation method thereof. Background Art

[0002] Probiotics are active microorganisms. The lactobacilli they contain are the most numerous flora in the vagina of normal women. They can produce substances such as lactic acid, hydrogen peroxide and some enzymes, and are an important guarantee for maintaining the stability of the vaginal microecological environment. Therefore, it is generally believed that adding probiotics can achieve the purpose of enhancing the efficacy of sanitary napkins, maintain the balance of vaginal flora, and keep the female reproductive environment healthy.

[0003] Non-woven fabric is a non-woven fabric that directly uses polymer chips, short fibers or filaments to form a web through airflow or machinery, and then reinforces it through hydroentanglement, needle punching, or hot rolling, and finally forms a non-woven fabric through post-finishing. It is a new type of fiber product with soft, breathable and planar structure. The advantages are that it does not produce fiber scraps, is strong, durable and soft. It is also a kind of reinforcing material and has a cotton feel.

[0004] Probiotic sanitary napkins are an upgrade of traditional sanitary napkin fabrics. The surface layer of the sanitary napkins containing probiotics is hot air non-woven fabric. Hot air non-woven fabric is made by combing ES fibers and using hot air from a drying device to penetrate the fiber web, causing it to be heated and bonded.

[0005] In the prior art, a Chinese invention patent with application number CN201310028575X discloses a non-woven fabric with biological regulation effect, wherein the non-woven fabric is treated with a finishing agent prepared by a functional combination liquid, wherein the functional combination liquid contains oligosaccharides and probiotic metabolites in a weight-volume ratio of 25%-60%, and 5%-30% probiotic metabolites, and the functional combination liquid accounts for 7-20% of the weight of the finishing agent. The non-woven fabric is treated with a finishing agent prepared by a functional combination liquid containing probiotics, and then air-dried or dried. The non-woven fabric surface is directly finished by probiotics, which easily causes the probiotics to be inactivated, resulting in a reduction in effective ingredients and insufficient durability. The non-woven fabric is impregnated with an impregnation liquid containing microbial capsules, and the probiotics are protected by the microcapsule shell, which brings high temperature resistance and extends the storage time of the probiotics. However, the adsorption between the probiotic microcapsules and the non-woven fabric is poor, which makes the probiotic microcapsules easy to fall off, resulting in a significant reduction in the stability of the probiotic non-woven fabric. However, the use of adhesives to fix the probiotic microcapsules will cause the softness and comfort of the non-woven fabric to be lost. Summary of the invention

[0006] In order to improve the activity retention rate of probiotics in non-woven sanitary products, the present application provides a probiotic sanitary product and a preparation method thereof.

[0007] In the first aspect, the present application provides a probiotic sanitary product, which adopts the following technical solution:

[0008] A probiotic hygienic product comprises a probiotic non-woven fabric, wherein the probiotic non-woven fabric contains fibers rich in probiotics, and the fibers rich in probiotics are prepared by the following method:

[0009] Sodium alginate is dissolved to prepare a solution A with a concentration of 2.5-3 wt %, polyvinyl alcohol is dissolved to prepare a solution B with a solubility of 4-5 wt %, and solution A and solution B are mixed at a mass ratio of 1:1.3-1.5 to prepare a shell solution;

[0010] The bacterial solution containing probiotics is added to solution B with a concentration of 4-5wt% to prepare a nuclear layer solution, wherein the mass ratio of the bacterial solution containing probiotics to solution B is 1:20-25, and soy protein isolate and calcium chloride are mixed and dissolved in a mass ratio of 1:0.6-0.8 to prepare a receiving solution;

[0011] The shell layer solution and the core layer solution are sprayed into the receiving solution by coaxial electrostatic spraying, filtered, and dried to obtain probiotic embedded particles;

[0012] The polyethersulfone is dissolved to prepare an electrospinning solution with a concentration of 18-22 wt%, and electrospinning is performed to prepare a polyethersulfone nanofiber membrane;

[0013] The probiotic embedded particles are added to a pectin solution with a concentration of 5-6wt% to prepare a spray liquid, the mass ratio of the probiotic embedded particles to the pectin solution is 1:0.1-0.2, the spray liquid is evenly sprayed on the polyethersulfone nanofiber membrane in 3-7 times, dried, and crushed to prepare a blended powder, and the mass ratio of the spray liquid sprayed once to the polyethersulfone nanofiber membrane is 0.1-0.15:1;

[0014] The blended powder is mixed with PE resin and additives in a mass ratio of 1:5-10:0.2-0.5, extruded and granulated to obtain a shell material, and the shell material and PET slices are composite spun, wound, bundled, stretched, heat-set, curled and cut in a mass ratio of 1-1.2:1 to obtain fibers rich in probiotics.

[0015] By adopting the above technical scheme, sodium alginate and polyvinyl alcohol are used as shell layer solutions, polyvinyl alcohol solution is mixed with bacterial solution containing probiotics as core layer solution, soy protein isolate solution containing calcium chloride is used as receiving solution, and coaxial electrostatic spraying is adopted. Under the action of electrostatic field, droplets formed at the needle tip are vertically dripped into the soy protein isolate receiving solution, a cross-linking reaction occurs, and a layer of soy protein isolate molecules is adsorbed on the outside of the microcapsule, and finally a multi-layer microcapsule with probiotics embedded in the core is formed. Sodium alginate and polyvinyl alcohol are compounded as shell layer wall materials, which can improve the mechanical properties of embedded particles and improve stability. In addition, the electrostatic attraction between soy protein isolate and sodium alginate is improved. The embedded particles are coated with a layer of soy protein isolate molecules, which improves the performance of the embedded particles and the heat protection ability of the embedded particles themselves. In addition, the embedded particles have a high pyrolysis temperature and have a certain tolerance to extremely hot environments, which can improve the high-temperature storage stability of the probiotic embedded particles during subsequent production and storage; the probiotic embedded particles are then sprayed on the polyethersulfone nanofiber membrane using pectin solution. Polyethersulfone has good chemical and hydrolytic stability and high strength. The fiber membrane formed by electrospinning is not only of high quality and good permeability, but also has a large specific surface area, high porosity, and good connectivity of the internal voids. However, the chemical structure of polyethersulfone lacks hydroxyl and carboxyl groups. , amino, thiol and other hydrophilic groups, thus showing strong hydrophobicity. By spraying, the pectin solution containing probiotic embedded particles is attached to the polyethersulfone nanofiber membrane. The spraying liquid enters the polyethersulfone nanofiber membrane through absorption and penetration. The pectin connects the polyethersulfone nanofibers to each other, increasing the interaction force between the probiotic embedded particles and the polyethersulfone nanofibers, while improving the hydrophilicity of the polyethersulfone nanofiber membrane and the loading fastness of the embedded particles. The polyethersulfone nanofibers are intertwined with each other, with larger pores, forming a relatively loose three-dimensional network structure, which is convenient for the loading of probiotic embedded particles, and the polyethersulfone nanofibers The membrane as a carrier material has high porosity and high specific surface area, which is suitable for the growth and reproduction of probiotics. The three-dimensional porous structure provides abundant adhesion sites and growth space, and the perfect size match with microbial cells and the difference in hydrophilicity and hydrophobicity with microorganisms serve as a strong driving force, which promotes the probiotics to quickly form a dense biofilm. The network structure of the polyethersulfone nanofiber membrane further provides high temperature protection for the probiotics. The obtained blended powder is blended and granulated with PE resin to obtain the shell material. PET is used as the core layer, and composite spinning is performed to form ES fiber, which has the advantages of softness, breathability and skin-friendliness. Moreover, after multiple protections, the survival rate of probiotics is high and the activity is preserved for a long time.

[0016] Optionally, hydroxyapatite is further added to the electrospinning solution, the mass ratio of hydroxyapatite to polyethersulfone is 0.1-0.15:1, and the hydroxyapatite is pretreated as follows:

[0017] Add hydroxyapatite to the wool protein solution, mix well and then perform rotary evaporation, then pre-freeze at - (18-20) ° C for 10-12 hours, vacuum dry for 70-72 hours, immerse in a silver nitrate solution with a concentration of 1-2 g / mL, stir at room temperature for 6-7 hours in a dark place, wash, dry and grind, and the mass ratio of hydroxyapatite to wool protein solution is 1:3-5.

[0018] By adopting the above technical scheme, the surface contact angle of polyethersulfone is large and it is hydrophobic, which has an adverse effect on the hygroscopicity and water holding capacity of the finished fiber, and the addition of hydroxyapatite can improve the hydrophilicity of the polyethersulfone nanofiber membrane, but there is a problem of poor interface compatibility between hydroxyapatite and polyethersulfone, which will lead to the deterioration of the mechanical properties of the polyethersulfone nanofiber. Wool protein, as an amorphous natural polymer, has biological activity and controllable degradability. The composite of hydroxyapatite and wool protein can improve the surface activity and biocompatibility of hydroxyapatite, and wool protein is easily mixed with polyethersulfone, which can improve the mechanical properties of polymer materials. After the wool protein and hydroxyapatite are mixed and freeze-dried, there is a strong interaction between the amide group and calcium ions in the keratin molecular chain to form a porous structure, thereby improving the interface bonding between hydroxyapatite and polyethersulfone, making the nanofiber The surface of the rice fiber membrane is smoother, the pretreated hydroxyapatite has a strong adhesion to the polyethersulfone nanofibers, and there will be no large-scale agglomeration in the electrospinning solution. In addition, the pretreated hydroxyapatite has a toughening effect on the polyethersulfone nanofibers. The melting point of hydroxyapatite is 1650°C, and the thermal decomposition temperature of wool protein is low. After combining with hydroxyapatite, the thermal stability is increased. Therefore, the addition of hydroxyapatite increases the thermal stability of the probiotic embedded particles embedded in the polyethersulfone nanofiber membrane and reduces the effect of temperature on the activity of probiotics. Finally, the porous structure formed by wool protein and hydroxyapatite is used to impregnate silver nitrate to obtain a silver-loaded hydroxyapatite / wool protein complex, thereby improving the antibacterial effect of the polyethersulfone nanofiber membrane, thereby increasing the antibacterial and protective effect of the finished fiber, and improving the use effect of the finished fiber in disposable sanitary products.

[0019] Optionally, fish oil and lactitol are further added to the core layer solution, and the mass ratio of fish oil, lactitol and bacterial solution containing probiotics is 0.1-0.3:0.15-0.2:1.

[0020] By adopting the above technical scheme, fish oil and lactitol are used as prebiotics, which are not only beneficial to the growth and adhesion of probiotics, but also can increase the encapsulation effect of the shell solution on the probiotics. Fish oil can interact with the shell solution to make the formed encapsulation structure more compact, thereby improving the survival ability of the probiotics. In addition, lactitol is a high-temperature resistant probiotic, and when combined with fish oil, it adds an oily protective layer to the encapsulated particles, thereby enhancing the stability of the encapsulated particles in extremely hot environments and enhancing the thermal stability of the probiotics.

[0021] Optionally, the solvent used for dissolving the polyethersulfone is dimethylformamide and acetone in a mass ratio of 1.7:0.3-0.5.

[0022] By adopting the above technical scheme, the use of DMF can improve the stretching state of the polymer chain and make the molecular chain have good fluidity in the electrospinning solution, while AC, as a poor solvent for polyethersulfone, can make the originally stretched molecular chain segments appear to have a certain degree of contraction, strengthen the mutual entanglement between the polyethersulfone molecular chains, increase the viscosity of the spinning solution, and improve the intermolecular entanglement, which is beneficial to reduce the formation of beads, thereby making the diameter of the formed polyethersulfone nanofibers more uniform.

[0023] Optionally, the electrostatic spraying pressure is 9-10 kV, the flow rate of the shell solution is 5-7 mL / h, the flow rate of the core solution is 3-4 mL / h, and the distance between the spraying needle and the receiving liquid surface is 10-12 cm;

[0024] During the electrospinning, the receiving distance is 14-15 cm, the spinning voltage is 14-15 kV, and the spinning speed is 0.04-0.06 mL / h;

[0025] The temperature of the composite spinning is 285-290° C., and the cutting length is 50-51 mm.

[0026] By adopting the above technical scheme, if the voltage is too high during electrostatic spraying, the particle size of the embedded particles will be reduced or even unable to form, the thickness of the capsule wall will be reduced, and the protective effect on the probiotics will be reduced. If the flow rate is too slow, the shell cannot be formed evenly, resulting in uneven thickness. If the receiving distance is too large during electrostatic spinning, the jet will be over-stretched, the fiber diameter will be too small, and the increase in voltage will cause the fiber diameter to be too large. During composite spinning, if the temperature is too high, the material will be degraded, affecting the thermal stability and mechanical properties of the fiber. If the temperature is too low, the viscosity of the spinning raw material will increase, making it difficult to spin, and the internal structure of the fiber will be uneven.

[0027] Optionally, the probiotic is selected from at least one of Lactobacillus acidophilus, Lactobacillus bulgaricus, Lactobacillus fermentum, Lactobacillus rhamnosus, Bifidobacterium bifidum and Bifidobacterium longum.

[0028] By adopting the above technical scheme, Lactobacillus acidophilus can inhibit the reproduction of Candida albicans in the vagina and maintain the balance of vaginal microecology. It makes the vaginal environment acidic by producing substances such as lactic acid, creates an environment that is not conducive to the growth of harmful bacteria, improves women's vaginal health, and prevents and improves gynecological diseases; Lactobacillus bulgaricus can regulate vaginal flora, improve local vaginal immunity, and reduce the risk of infection. Lactobacillus fermentum can synergize with other beneficial bacteria to jointly maintain the balance of vaginal microecology, and the metabolites it produces have antibacterial effects and can inhibit the growth of harmful bacteria; Lactobacillus rhamnosus can reduce the number of harmful bacteria, improve the vaginal flora environment, and relieve the symptoms of vaginitis; Bifidobacterium bifidum and Bifidobacterium longum can provide favorable conditions for vaginal health, so that the finished fiber has a better protective effect on women's reproductive health when used to prepare sanitary napkins.

[0029] Optionally, the probiotic non-woven fabric further contains bamboo charcoal fiber and bacterial cellulose, and the mass ratio of the bamboo charcoal fiber, bacterial cellulose and probiotic-rich fiber is 2-3:1-2:7.

[0030] By adopting the above technical scheme, the bamboo charcoal fiber has a honeycomb microporous structure, which increases its specific surface area and provides more adsorption sites for it, so that it has good water absorption and air permeability, and also has antibacterial effect and high strength, which can improve the air permeability, hygroscopicity and antibacterial rate of non-woven fabrics. Bacterial cellulose is a natural nanofiber with an ultra-fine three-dimensional network structure, strong air permeability, high water holding capacity, and a certain antibacterial effect. When the non-woven fabric is used as the surface layer of the sanitary napkin, the bamboo charcoal fiber and bacterial cellulose can increase the liquid absorption and water locking effect of the sanitary napkin, so that the sanitary napkin does not leak or overflow. The water is not only stored in the dense three-dimensional network pore structure of the non-woven fabric, but also can be combined with a large number of hydroxyl groups on the bacterial cellulose through hydrogen bonding, so that more water molecules are fixed, thereby increasing the water locking effect of the sanitary napkin and keeping it dry and breathable.

[0031] In a second aspect, the present application provides a method for preparing a probiotic sanitary product, using the following technical solution:

[0032] A method for preparing a probiotic sanitary product comprises the following steps:

[0033] S1. Preparing a probiotic non-woven fabric: opening, fine opening, combing, cross-laying and drafting the probiotic-rich fiber to obtain a probiotic fiber web;

[0034] The bamboo charcoal fibers are subjected to opening, fine opening, combing, cross-laying and drafting to obtain a bamboo charcoal fiber web;

[0035] The probiotic fiber net and the bamboo charcoal fiber net are overlapped into one by hydroentanglement, and dried at 130-140° C. to obtain a base fabric;

[0036] The bacterial cellulose and distilled water are mixed at a mass ratio of 1:500-600, and nano-milled to obtain a dispersion, sodium periodate is added, and the mixture is stirred at 50-55° C. for 3-4 hours, and an acetic acid solution of chitosan is added, and the mixture is reacted at 60-65° C. for 2-3 hours, centrifuged, and washed to obtain oxidized bacterial cellulose, and then dispersed in a hyaluronic acid solution with a concentration of 0.5-1wt%, and ultrasonicated at 750-800W and 15-20kHz for 1.5-2min to obtain a treatment solution with an oxidized bacterial cellulose concentration of 0.4-0.5wt%, and the treatment solution is evenly sprayed on both sides of the base fabric, and dried to obtain a probiotic non-woven fabric;

[0037] S2. Preparation of sanitary products: using the probiotic non-woven fabric as the surface material of the sanitary products, and preparing the probiotic sanitary products according to the production method of the sanitary products.

[0038] By adopting the above technical scheme, the probiotic fiber net and the bamboo charcoal fiber net are spunlace to form a base cloth, which can increase the mutual entanglement of the probiotic-rich fiber and the bamboo charcoal fiber to form a base cloth with certain strength and complete structure. Then, high temperature is used for drying. The high temperature causes the PE resin as the shell material in the probiotic-rich fiber to melt and play a bonding role, so that the probiotic-rich fiber and the bamboo charcoal fiber are bonded. The blended powder in the shell material can flow with the hot-melt PE resin when the PE resin is hot-melted, so as to be evenly distributed on the base cloth. Chitosan is a linear copolymer composed of aminoglucose units, which has unique film-forming properties and antibacterial activity. First, bacterial cellulose is oxidized by sodium periodate to form dialdehyde cellulose, and then the aldehyde group of the dialdehyde cellulose is grafted and connected with the amino group of chitosan by Schiff base reaction, so as to improve the dispersibility of bacterial cellulose. In addition, part of chitosan is coated on the surface of bacterial cellulose by physical adsorption. As a lubricant and stabilizer of bacterial cellulose, chitosan forms a lubricating film on the surface of bacterial cellulose. The friction between fibers is reduced, the dispersibility is improved, the specific surface area of ​​the fibers is increased, the stability is enhanced, and the grafting effect increases the spatial steric hindrance of the molecular chain, thereby improving the dispersibility of the bacterial cellulose. Therefore, the oxidized bacterial cellulose obtained has good dispersibility, and is dispersed in a hyaluronic acid solution. Through ultrasonic cavitation, the oxidized bacterial cellulose is dispersed in the hyaluronic acid solution to form a stable and uniform suspension, and the ultrasonic effect forms cellulose nanofibrils from the oxidized bacterial cellulose. The hyaluronic acid is a high molecular weight hyaluronic acid, which has a strong antibacterial effect and a strong adhesion effect, which can increase the adhesion of the treatment liquid on the base fabric. Moreover, hyaluronic acid has high hydrophilicity and can add more hydrogen bonds in the network structure of the non-woven fabric to lock in moisture. The chelating effect on water molecules is stronger than that of cellulose, thereby firmly locking the water molecules in the amorphous region inside the non-woven fabric, enhancing the water-locking effect of the probiotic sanitary napkin. Moreover, the density of the non-woven fabric increases after spraying, which can more effectively lock in moisture and prevent overflow, thereby reducing the side leakage of the sanitary napkin. Sanitary products made of fibers rich in probiotics are not only rich in probiotics, which can effectively increase the use effect of sanitary products, but also softer, more comfortable, skin-friendly, and breathable, increasing the comfort of use.

[0039] In summary, this application has the following beneficial effects:

[0040] 1. Since the present application uses sodium alginate and polyvinyl alcohol as the shell layer, the polyvinyl alcohol solution containing probiotics as the core layer, and soy protein and calcium chloride as the receiving liquid, probiotic embedded particles with a multilayer structure are formed, which improves the heat resistance and storage stability of the probiotics. Then, the three-dimensional network structure of the polyethersulfone nanofiber membrane is used to load and protect the probiotic embedded particles. The three-dimensional network structure forms multiple protections, which increases the heat resistance protection of the probiotics. Finally, PE resin is used as the shell layer and PET is used as the core layer to obtain ES fibers with a high probiotic survival rate and good storage stability. The probiotic sanitary products made therefrom have a high probiotic survival rate and are soft and comfortable.

[0041] 2. In the present application, wool protein is preferably used to pretreat hydroxyapatite, and a porous structure is formed after freeze-drying, thereby improving the dispersibility of hydroxyapatite in the electrospinning solution, thereby increasing the hydrophilicity of polyethersulfone and improving the moisture retention of the finished fiber. In addition, the porous structure is impregnated with silver nitrate solution to enhance the antibacterial ability of the polyethersulfone nanofiber membrane, thereby improving the antibacterial effect of the finished fiber.

[0042] 3. In the present application, fish oil and lactitol are preferably added to the core layer solution, which can improve the density of the probiotic embedded particles, while increasing the heat resistance of the embedded particles and increasing the storage stability.

[0043] 4. In this application, it is preferred to use probiotic-rich fibers, bamboo charcoal fibers, and bacterial cellulose to prepare probiotic non-woven fabrics. The antibacterial properties and high water absorption of bamboo charcoal fibers and bacterial cellulose can enhance the inhibitory effect of probiotic non-woven fabrics on various harmful bacteria, and can increase the water-locking and moisturizing ability of probiotic non-woven fabrics, and increase the dry effect of probiotic non-woven fabrics when used as sanitary napkins. DETAILED DESCRIPTION

[0044] The following examples further illustrate the present application in detail.

[0045] Example of preparation of fiber rich in probiotics

[0046] Preparation Example 1: S1, 3 g of sodium alginate was dissolved in deionized water to prepare a solution A with a concentration of 3 wt%, 5 g of polyvinyl alcohol was dissolved in deionized water to prepare a solution B with a concentration of 5 wt%, and the solution A and the solution B were mixed uniformly at a mass ratio of 1:1.3 to prepare a shell solution, wherein the polyvinyl alcohol was PVA1788;

[0047] S2. Add Lactobacillus acidophilus stored at -20°C to MRS medium, culture at 37°C for 18 h, activate twice, and then centrifuge at 5000 rpm and 4°C for 5 min. Collect the precipitate, wash with sterile saline, and dilute with saline until the colony count is greater than 1×10 11cfu / g of a probiotic-containing bacterial solution; adding the probiotic-containing bacterial solution to a solution B having a concentration of 5wt%, mixing, and preparing a nuclear layer solution, wherein the mass ratio of the probiotic-containing bacterial solution to the solution B is 1:20, and the Lactobacillus acidophilus is selected from Xi'an Youlanda Biotechnology, and the product number is YLD-101405;

[0048] S3, adding 2.5g of soy protein isolate and calcium chloride into deionized water, stirring overnight to prepare a receiving solution, wherein the mass ratio of soy protein isolate to calcium chloride in the receiving solution is 1:0.6, and the concentration of soy protein isolate is 2.5wt%;

[0049] S4, spraying the shell layer solution and the core layer solution into the receiving solution by coaxial electrostatic spraying, the spraying voltage is 9 kV, the flow rate of the shell layer solution is 7 m / h, the flow rate of the core layer solution is 3 mL / h, the distance between the needle and the upper surface of the receiving solution is 10 cm during spraying, filtering, and drying at 60° C. to obtain probiotic embedded particles;

[0050] S5, dissolving 3.7g of polyethersulfone in a solvent to prepare an electrospinning solution with a concentration of 18wt%, and then electrospinning to obtain a polyethersulfone nanofiber membrane, the Mw of the polyethersulfone is 45000, selected from BASF, Germany, the solvent is dimethylformamide and acetone with a mass ratio of 1.7:0.3, the electrospinning pressure is 15kV, the spinning speed is 0.04mL / h, the receiving distance is 14cm, the spinning time is 1.5h, and the thickness of the polyethersulfone nanofiber membrane is 100μm;

[0051] S6, adding 10g of probiotic embedded particles to a 6wt% aqueous solution of pectin to prepare a spray liquid, the mass ratio of the probiotic embedded particles to the pectin solution is 0.2:1, the spray liquid is evenly sprayed on the polyethersulfone nanofiber membrane 7 times, the mass ratio of the spray liquid to the polyethersulfone nanofiber membrane is 0.1:1, dried at 60°C, and then crushed to obtain a blended powder with a particle size of 10μm;

[0052] S7, 20g of the blended powder was mixed with PE resin and an additive in a mass ratio of 1:5:0.5, and the mixture was melted and granulated to obtain a shell material, the extrusion temperature was 200°C, the additive was antioxidant 1010, and the PE resin was HDPE, selected from Fushun Petrochemical, with a grade of 2911; the shell material and PET slices were composite spun in a mass ratio of 1.2:1, and the fibers rich in probiotics were obtained by winding, bundling, stretching, heat setting, curling, and cutting. The PET slices were selected from Hengshui Qinghua Plastic Factory, Jizhou District, City, product number is PET-QH, brand name is Qh-pet, spinning temperature is 280℃, cutting length is 50mm, side blowing temperature is 14℃, side blowing humidity is 85%, main pressure of crimping machine is 0.14MPa, side pressure is 0.15MPa, back pressure is 0.1MPa, winding speed is 1.2kg / min, stretching multiple is 3.5, stretching temperature is 78℃, heat setting temperature is 110℃ for zone one, 105℃ for zone two, and 105℃ for zone three.

[0053] Preparation Example 2: S1, dissolving 2.5 g of sodium alginate in deionized water to prepare a solution A with a concentration of 2.5 wt%, dissolving 4 g of polyvinyl alcohol in deionized water to prepare a solution B with a concentration of 4 wt%, and mixing solution A and solution B in a mass ratio of 1:1.5 to prepare a shell solution, wherein the polyvinyl alcohol is PVA1788;

[0054] S2. Add Lactobacillus bulgaricus stored at -20°C to MRS medium, culture at 37°C for 18 h, activate twice, and then centrifuge at 5000 rpm and 4°C for 5 min. Collect the precipitate, wash with sterile saline, and dilute with saline until the colony count is greater than 1×10 11 cfu / g of a probiotic-containing bacterial solution; adding the probiotic-containing bacterial solution to a solution B having a concentration of 4wt%, mixing, and preparing a nuclear layer solution, the mass ratio of the probiotic-containing bacterial solution to the solution B is 1:25, and the Bulgarian Lactobacillus is selected from Xi'an Rongzhen Biotechnology, and the item number is RZ-BJLYRGJ;

[0055] S3, adding 2.5g of soy protein isolate and calcium chloride into deionized water, stirring overnight to prepare a receiving solution, wherein the mass ratio of soy protein isolate to calcium chloride in the receiving solution is 1:0.8, and the concentration of soy protein isolate is 2.5wt%;

[0056] S4, spraying the shell layer solution and the core layer solution into the receiving solution by coaxial electrostatic spraying, the spraying voltage is 10 kV, the flow rate of the shell layer solution is 5 m / h, the flow rate of the core layer solution is 4 mL / h, the distance between the needle and the upper surface of the receiving solution is 12 cm during spraying, filtering, and drying at 60° C. to obtain probiotic embedded particles;

[0057] S5, dissolving 3.7g of polyethersulfone in a solvent to prepare an electrospinning solution with a concentration of 22wt%, and then electrospinning to obtain a polyethersulfone nanofiber membrane, the Mw of the polyethersulfone is 45000, selected from BASF, Germany, the solvent is dimethylformamide and acetone with a mass ratio of 1.7:0.5, the electrospinning pressure is 14kV, the spinning speed is 0.06mL / h, the receiving distance is 15cm, the spinning time is 1.5h, and the thickness of the polyethersulfone nanofiber membrane is 100μm;

[0058] S6, adding 10g of probiotic embedded particles to a 5wt% aqueous solution of pectin to prepare a spray liquid, the mass ratio of the probiotic embedded particles to the pectin solution is 0.1:1, and the spray liquid is evenly sprayed on the polyethersulfone nanofiber membrane three times, the mass ratio of the spray liquid to the polyethersulfone nanofiber membrane is 0.15:1, and dried at 60°C, and then crushed to obtain a blended powder with a particle size of 20μm;

[0059] S7, 20g of the blended powder was mixed with PE resin and an auxiliary agent in a mass ratio of 1:10:0.2, and the mixture was melted and granulated to obtain a shell material, the extrusion temperature was 210°C, the auxiliary agent was antioxidant 1010, and the PE resin was HDPE, selected from Fushun Petrochemical, with a grade of 2911; the shell material and PET slices were composite spun in a mass ratio of 1:1, and the fibers rich in probiotics were obtained by winding, bundling, stretching, heat setting, curling, and cutting, and the PET slices were selected from Hengshui City Jizhou District Qinghua Plastic Factory, product number is PET-QH, brand name is Qh-pet, spinning temperature is 280℃, cutting length is 50mm, side blowing temperature is 14℃, side blowing humidity is 85%, main pressure of crimping machine is 0.14MPa, side pressure is 0.15MPa, back pressure is 0.1MPa, winding speed is 1.2kg / min, stretching multiple is 3.5, stretching temperature is 78℃, heat setting temperature is 110℃ for zone one, 105℃ for zone two, and 105℃ for zone three.

[0060] Preparation Example 3: S1, dissolving 2.8 g of sodium alginate in deionized water to prepare a solution A with a concentration of 2.8 wt%, dissolving 4.5 g of polyvinyl alcohol in deionized water to prepare a solution B with a concentration of 4.5 wt%, and mixing solution A and solution B in a mass ratio of 1:1.4 to prepare a shell solution, wherein the polyvinyl alcohol is PVA1788;

[0061] S2. Add Lactobacillus rhamnosus stored at -20°C to MRS medium, culture at 37°C for 18 h, activate twice, and then centrifuge at 5000 rpm and 4°C for 5 min. Collect the precipitate, wash with sterile saline, and dilute with saline until the colony count is greater than 1×10 11cfu / g of a probiotic-containing bacterial solution; adding the probiotic-containing bacterial solution to a solution B having a concentration of 4.5wt%, mixing, and preparing a nuclear layer solution, the mass ratio of the probiotic-containing bacterial solution to the solution B is 1:23, and Lactobacillus rhamnosus is selected from Xi'an Youlanda Biotechnology, with a product number of YLD-101371;

[0062] S3, adding 2.5g of soy protein isolate and calcium chloride into deionized water, stirring overnight to prepare a receiving solution, wherein the mass ratio of soy protein isolate to calcium chloride in the receiving solution is 1:0.7, and the concentration of soy protein isolate is 2.5wt%;

[0063] S4, spraying the shell layer solution and the core layer solution into the receiving solution by coaxial electrostatic spraying, the spraying voltage is 10 kV, the flow rate of the shell layer solution is 6 m / h, the flow rate of the core layer solution is 3.5 mL / h, the distance between the needle and the upper surface of the receiving solution is 11 cm during spraying, filtering, and drying at 60° C. to obtain probiotic embedded particles;

[0064] S5, dissolving 3.7g of polyethersulfone in a solvent to prepare an electrospinning solution with a concentration of 20wt%, and then electrospinning to obtain a polyethersulfone nanofiber membrane, the Mw of the polyethersulfone is 45000, selected from BASF, Germany, the solvent is dimethylformamide and acetone with a mass ratio of 1.7:0.4, the electrospinning pressure is 14kV, the spinning speed is 0.05mL / h, the receiving distance is 15cm, the spinning time is 1.5h, and the thickness of the polyethersulfone nanofiber membrane is 100μm;

[0065] S6, adding 10g of probiotic embedded particles to a 5.5wt% aqueous solution of pectin to prepare a spray liquid, the mass ratio of the probiotic embedded particles to the pectin solution is 0.15:1, and the spray liquid is evenly sprayed on the polyethersulfone nanofiber membrane three times, the mass ratio of the spray liquid to the polyethersulfone nanofiber membrane is 0.13:1, and dried at 60°C, and then crushed to obtain a blended powder with a particle size of 15μm;

[0066] S7, 20g of the blended powder was mixed with PE resin and an auxiliary agent in a mass ratio of 1:8:0.3, and the mixture was melted and granulated to obtain a shell material, the extrusion temperature was 210°C, the auxiliary agent was antioxidant 1010, and the PE resin was HDPE, selected from Fushun Petrochemical, with a grade of 2911; the shell material and PET slices were composite spun in a mass ratio of 1.1:1, and the fibers rich in probiotics were obtained by winding, bundling, stretching, heat setting, curling, and cutting. The PET slices were selected from Hengshui Qinghua Plastic Factory, Jizhou District, City, product number is PET-QH, brand name is Qh-pet, spinning temperature is 280℃, cutting length is 50mm, side blowing temperature is 14℃, side blowing humidity is 85%, main pressure of crimping machine is 0.14MPa, side pressure is 0.15MPa, back pressure is 0.1MPa, winding speed is 1.2kg / min, stretching multiple is 3.5, stretching temperature is 78℃, heat setting temperature is 110℃ for zone one, 105℃ for zone two, and 105℃ for zone three.

[0067] Preparation Example 4: The difference from Preparation Example 1 is that in step S5, hydroxyapatite is further added to the electrospinning solution, the mass ratio of hydroxyapatite to polyethersulfone is 0.15:1, and the hydroxyapatite is pretreated as follows:

[0068] Put 2.5g of short wool into 50mL of mixed aqueous solution containing 0.95g of sodium sulfide, 0.4 sodium dodecyl sulfate and 21g of urea, dissolve at 35°C, filter, dialyze with nanofiltration membrane, adjust the pH to neutral, and obtain a wool protein solution with a mass concentration of 0.1g / mL. Add hydroxyapatite thereto, mix well and remove the solvent by rotary evaporation, pre-freeze at -18°C for 12h, and then vacuum dry for 72h. Then immerse in a silver nitrate solution with a concentration of 2g / mL, stir at room temperature for 6h in the dark, wash, dry, and grind to 200nm. The mass ratio of hydroxyapatite to wool protein solution is 1:5.

[0069] Preparation Example 5: In step S5, hydroxyapatite is further added to the electrospinning solution, the mass ratio of hydroxyapatite to polyethersulfone is 0.1:1, and the hydroxyapatite is pretreated as follows:

[0070] Put 2.5g of short wool into 50mL of mixed aqueous solution containing 0.95g of sodium sulfide, 0.4 sodium dodecyl sulfate and 21g of urea, dissolve at 35°C, filter, dialyze with nanofiltration membrane, and adjust the pH to neutral to obtain a wool protein solution with a mass concentration of 0.1g / mL. Add hydroxyapatite thereto, mix well and remove the solvent by rotary evaporation, pre-freeze at -20°C for 10h, and then vacuum dry for 70h. Then immerse in a silver nitrate solution with a concentration of 1g / mL, stir at room temperature for 7h in the dark, wash, dry, and grind to 200nm. The mass ratio of hydroxyapatite to wool protein solution is 1:3.

[0071] Preparation Example 6: The difference from Preparation Example 4 is that in step S5, hydroxyapatite is further added to the electrospinning solution, the mass ratio of hydroxyapatite to polyethersulfone is 0.15:1, and the hydroxyapatite is pretreated as follows:

[0072] Put 2.5g of short wool into 50mL of mixed aqueous solution containing 0.95g of sodium sulfide, 0.4 sodium dodecyl sulfate and 21g of urea, dissolve it at 35°C, filter and dialyze it with nanofiltration membrane, adjust the pH to neutral, and obtain a wool protein solution with a mass concentration of 0.1g / mL. Add hydroxyapatite thereto, mix well and remove the solvent by rotary evaporation, pre-freeze it at -18°C for 12h, then vacuum dry it for 72h, grind it to 200nm, and the mass ratio of hydroxyapatite to wool protein solution is 1:5.

[0073] Preparation Example 7: The difference from Preparation Example 4 is that in step S5, hydroxyapatite is further added to the electrospinning solution, the mass ratio of hydroxyapatite to polyethersulfone is 0.15:1, and the hydroxyapatite is pretreated as follows:

[0074] The hydroxyapatite was immersed in a silver nitrate solution with a concentration of 2 g / mL, stirred at room temperature for 6 h in the dark, washed, dried, and ground to 200 nm.

[0075] Preparation Example 8: The difference from Preparation Example 4 is that in step S5, hydroxyapatite is further added to the electrospinning solution, and the mass ratio of hydroxyapatite to polyethersulfone is 0.15:1.

[0076] Preparation Example 9: The difference from Preparation Example 4 is that in step S2, when preparing the nuclear layer solution, fish oil and lactitol are added to the nuclear layer solution, and the mass ratio of fish oil, lactitol and bacterial solution containing probiotics is 0.3:0.2:1.

[0077] Preparation Example 10: The difference from Preparation Example 4 is that in step S2, when preparing the nuclear layer solution, fish oil and lactitol are added to the nuclear layer solution, and the mass ratio of fish oil, lactitol and bacterial solution containing probiotics is 0.1:0.15:1.

[0078] Preparation Example 11: The difference from Preparation Example 10 is that in step S2, when preparing the nuclear layer solution, fish oil is added to the nuclear layer solution, and the mass ratio of fish oil to the bacterial solution containing probiotics is 0.3:1.

[0079] Preparation Example 12: The difference from Preparation Example 10 is that in step S2, when preparing the nuclear layer solution, lactitol is added to the nuclear layer solution, and the mass ratio of lactitol to the bacterial solution containing probiotics is 0.2:1.

[0080] Preparation Example 13: S1, 3 g of sodium alginate was dissolved in deionized water to prepare a solution A with a concentration of 3 wt%, 5 g of polyvinyl alcohol was dissolved in deionized water to prepare a solution B with a concentration of 5 wt%, and the solution A and the solution B were mixed uniformly at a mass ratio of 1:1.3 to prepare a shell solution, wherein the polyvinyl alcohol was PVA1788;

[0081] S2. Add Lactobacillus acidophilus stored at -20°C to MRS medium, culture at 37°C for 18 h, activate twice, and then centrifuge at 5000 rpm and 4°C for 5 min. Collect the precipitate, wash with sterile saline, and dilute with saline until the colony count is greater than 1×10 11 cfu / g of a bacterial solution containing probiotics; adding the bacterial solution containing probiotics to a solution B having a concentration of 5wt%, mixing, and preparing a nuclear layer solution, wherein the mass ratio of the bacterial solution containing probiotics to the solution B is 1:20;

[0082] S3, adding 2.5g of soy protein isolate and calcium chloride into deionized water, stirring overnight to prepare a receiving solution, wherein the mass ratio of soy protein isolate to calcium chloride in the receiving solution is 1:0.6, and the concentration of soy protein isolate is 2.5wt%;

[0083] S4, spraying the shell layer solution and the core layer solution into the receiving solution by coaxial electrostatic spraying, the spraying voltage is 9 kV, the flow rate of the shell layer solution is 7 m / h, the flow rate of the core layer solution is 3 mL / h, the distance between the needle and the upper surface of the receiving solution is 10 cm during spraying, filtering, and drying at 60° C. to obtain probiotic embedded particles;

[0084] S5, 20g of probiotic embedded particles are mixed with PE resin and auxiliary agent in a mass ratio of 1:5:0.5, and the mixture is melted and granulated by extrusion to obtain a shell material, the extrusion temperature is 200°C, the auxiliary agent is antioxidant 1010, and the PE resin is HDPE, which is selected from Fushun Petrochemical and has a brand number of 2911; the shell material and PET slices are composite spun in a mass ratio of 1.2:1, and the fibers rich in probiotics are obtained by winding, bundling, stretching, heat setting, curling, and cutting, and the PET slices are selected from Hengtai Qinghua Plastic Factory, Jizhou District, Shui City, product number is PET-QH, brand name is Qh-pet, spinning temperature is 280℃, cutting length is 50mm, side blowing temperature is 14℃, side blowing humidity is 85%, main pressure of crimping machine is 0.14MPa, side pressure is 0.15MPa, back pressure is 0.1MPa, winding speed is 1.2kg / min, stretching multiple is 3.5, stretching temperature is 78℃, heat setting temperature is 110℃ for zone one, 105℃ for zone two, and 105℃ for zone three.

[0085] Preparation Example 14: S1, 3 g of sodium alginate was dissolved in deionized water to prepare a solution A with a concentration of 3 wt%, 5 g of polyvinyl alcohol was dissolved in deionized water to prepare a solution B with a concentration of 5 wt%, and the solution A and the solution B were mixed uniformly at a mass ratio of 1:1.3 to prepare a shell solution, wherein the polyvinyl alcohol was PVA1788;

[0086] S2. Add Lactobacillus acidophilus stored at -20°C to MRS medium, culture at 37°C for 18 h, activate twice, and then centrifuge at 5000 rpm and 4°C for 5 min. Collect the precipitate, wash with sterile saline, and dilute with saline until the colony count is greater than 1×10 11 cfu / g of a bacterial solution containing probiotics; adding the bacterial solution containing probiotics to a solution B having a concentration of 5wt%, mixing, and preparing a nuclear layer solution, wherein the mass ratio of the bacterial solution containing probiotics to the solution B is 1:20;

[0087] S3, adding 2.5g of soy protein isolate and calcium chloride into deionized water, stirring overnight to prepare a receiving solution, wherein the mass ratio of soy protein isolate to calcium chloride in the receiving solution is 1:0.6, and the concentration of soy protein isolate is 2.5wt%;

[0088] S4, spraying the shell layer solution and the core layer solution into the receiving solution by coaxial electrostatic spraying, the spraying voltage is 9 kV, the flow rate of the shell layer solution is 7 m / h, the flow rate of the core layer solution is 3 mL / h, the distance between the needle and the upper surface of the receiving solution is 10 cm during spraying, filtering, and drying at 60° C. to obtain probiotic embedded particles;

[0089] S5, 3.7g polyethersulfone was dissolved in a solvent to prepare an electrospinning solution with a concentration of 18wt%, and probiotic embedded particles were added, the mass ratio of probiotic embedded particles to electrospinning solution was 0.2:1, mixed evenly and then electrospun to obtain a polyethersulfone nanofiber membrane, crushed to obtain a blended powder, the Mw of polyethersulfone was 45000, selected from BASF, Germany, the solvent was dimethylformamide and acetone in a mass ratio of 1.7:0.3, the electrospinning pressure was 15kV, the spinning speed was 0.04mL / h, the receiving distance was 14cm, the spinning time was 1.5h, the thickness of the polyethersulfone nanofiber membrane was 100μm, and the particle size of the blended powder was 10μm;

[0090] S6, 20g of the blended powder was mixed with PE resin and an auxiliary agent in a mass ratio of 1:5:0.5, and the mixture was melted and granulated to obtain a shell material, the extrusion temperature was 200°C, the auxiliary agent was antioxidant 1010, and the PE resin was HDPE, selected from Fushun Petrochemical, with a grade of 2911; the shell material and PET slices were composite spun in a mass ratio of 1.2:1, and the fibers rich in probiotics were obtained by winding, bundling, stretching, heat setting, curling, and cutting. The PET slices were selected from Hengshui Qinghua Plastic Factory, Jizhou District, City, product number is PET-QH, brand name is Qh-pet, spinning temperature is 280℃, cutting length is 50mm, side blowing temperature is 14℃, side blowing humidity is 85%, main pressure of crimping machine is 0.14MPa, side pressure is 0.15MPa, back pressure is 0.1MPa, winding speed is 1.2kg / min, stretching multiple is 3.5, stretching temperature is 78℃, heat setting temperature is 110℃ for zone one, 105℃ for zone two, and 105℃ for zone three.

[0091] Preparation Example 15: S1. Add Lactobacillus acidophilus stored at -20°C to MRS medium, culture at 37°C for 18 h, activate twice, and then centrifuge at 5000 rpm and 4°C for 5 min. Collect the precipitate, wash with sterile saline, and dilute with saline until the colony count is greater than 1×10 11 cfu / g of bacterial solution containing probiotics;

[0092] S2, 3.7g polyethersulfone was dissolved in a solvent to prepare an electrospinning solution with a concentration of 18wt%, and a bacterial solution containing probiotics was added to the electrospinning solution, the mass ratio of the bacterial solution containing probiotics to the electrospinning solution was 1:20, and then electrospinning was performed to obtain a polyethersulfone nanofiber membrane, which was crushed to obtain a blended powder, wherein the Mw of the polyethersulfone was 45000, selected from BASF, Germany, the solvent was dimethylformamide and acetone in a mass ratio of 1.7:0.3, the electrospinning pressure was 15kV, the spinning speed was 0.04mL / h, the receiving distance was 14cm, the spinning time was 1.5h, the thickness of the polyethersulfone nanofiber membrane was 100μm, and the blended crushed particle size was 10μm;

[0093] S3, 20g of the blended powder was mixed with PE resin and an auxiliary agent in a mass ratio of 1:5:0.5, and the mixture was melted and granulated to obtain a shell material, the extrusion temperature was 200°C, the auxiliary agent was antioxidant 1010, and the PE resin was HDPE, selected from Fushun Petrochemical, with a grade of 2911; the shell material and PET slices were composite spun in a mass ratio of 1.2:1, and the fibers rich in probiotics were obtained by winding, bundling, stretching, heat setting, curling, and cutting. The PET slices were selected from Hengshui Qinghua Plastic Factory, Jizhou District, City, product number is PET-QH, brand name is Qh-pet, spinning temperature is 280℃, cutting length is 50mm, side blowing temperature is 14℃, side blowing humidity is 85%, main pressure of crimping machine is 0.14MPa, side pressure is 0.15MPa, back pressure is 0.1MPa, winding speed is 1.2kg / min, stretching multiple is 3.5, stretching temperature is 78℃, heat setting temperature is 110℃ for zone one, 105℃ for zone two, and 105℃ for zone three.

[0094] Preparation Example 16: S1. Add Lactobacillus acidophilus stored at -20°C to MRS medium, culture at 37°C for 18 h, activate twice, and then centrifuge at 5000 rpm and 4°C for 5 min. Collect the precipitate, wash with sterile saline, and dilute with saline until the colony count is greater than 1×10 11 cfu / g of bacterial solution containing probiotics;

[0095] S2, 20g of probiotic-containing bacterial liquid was mixed with PE resin and auxiliary agent in a mass ratio of 1:5:0.5, and the mixture was melted and granulated to obtain a shell material, the extrusion temperature was 200°C, the auxiliary agent was antioxidant 1010, and the PE resin was HDPE, selected from Fushun Petrochemical, with a grade of 2911; the shell material and PET slices were composite spun in a mass ratio of 1.2:1, and the fibers rich in probiotics were obtained by winding, bundling, stretching, heat setting, curling, and cutting, and the PET slices were selected from Hengtai Qinghua Plastic Factory, Jizhou District, Shui City, product number is PET-QH, brand name is Qh-pet, spinning temperature is 280℃, cutting length is 50mm, side blowing temperature is 14℃, side blowing humidity is 85%, main pressure of crimping machine is 0.14MPa, side pressure is 0.15MPa, back pressure is 0.1MPa, winding speed is 1.2kg / min, stretching multiple is 3.5, stretching temperature is 78℃, heat setting temperature is 110℃ for zone one, 105℃ for zone two, and 105℃ for zone three.

[0096] Preparation Example 17: Lactobacillus acidophilus stored at -20°C was added to MRS medium, cultured at 37°C for 18 h, activated twice, and then centrifuged at 5000 rpm and 4°C for 5 min. The precipitate was collected, washed with sterile saline, and diluted with saline until the colony count was greater than 1×10 11cfu / g of bacterial solution containing probiotics;

[0097] Commercially available ES fiber (Jiangsu Zhongshi Fiber Co., Ltd., item number 10) was used, and the bacterial solution rich in probiotics was prepared by impregnation, rolling and drying. The rolling speed was 35m / min and the rolling pressure was 5kg / cm 2 ; The oven drying temperature is 100℃ and the drying time is 5min. Example

[0098] Example 1: A probiotic sanitary product, comprising a probiotic non-woven fabric, wherein the probiotic non-woven fabric is made of bamboo charcoal fiber, bacterial cellulose and probiotic-rich fiber prepared in Preparation Example 1 in a mass ratio of 3:1:7, and the bacterial cellulose is selected from Zhejiang Jinjiahao Green Nanomaterials, model CNF-BC.

[0099] The preparation method of the above-mentioned probiotic sanitary product comprises the following steps:

[0100] S1. Preparation of probiotic non-woven fabric:

[0101] (1) 700 g of the probiotic-rich fiber prepared in Preparation Example 1 was opened, finely opened, combed, cross-laid and drawn to prepare a probiotic fiber web;

[0102] (2) preparing a bamboo charcoal fiber web by opening, fine opening, combing, cross-laying and drafting 300 g of bamboo charcoal fiber;

[0103] (3) overlapping the probiotic fiber net and the bamboo charcoal fiber net by hydroentanglement, and drying at 140° C. to obtain a base fabric;

[0104] (4) 100 g of bacterial cellulose was mixed with distilled water at a mass ratio of 1:500, and then ground at 10 bar for 10 min, at 100 bar for 20 min, and finally at 400 bar for 60 min to prepare a dispersion;

[0105] (5) adding sodium periodate to the dispersion to make the sodium periodate concentration be 0.3 mol / l, stirring at 50°C for 4 h, adding a 2 wt% chitosan acetic acid solution, stirring at 60°C for 2 h, centrifuging, and washing with distilled water to obtain oxidized bacterial cellulose;

[0106] (6) Dispersing the oxidized bacterial cellulose in a hyaluronic acid aqueous solution with a concentration of 1 wt%, ultrasonically treating for 1.5 min at 800 W and 20 kHz to obtain a treatment solution with an oxidized bacterial cellulose concentration of 0.5 wt%, spraying the treatment solution evenly on both sides of the base fabric, and drying at 60 ° C to obtain a probiotic non-woven fabric. The hyaluronic acid was selected from Xi'an Ruien Biotechnology, with a molecular weight of 2.1 million and a product number of Rn512;

[0107] S2. Preparation of probiotic sanitary products: using the probiotic non-woven fabric as the surface material of the sanitary products, and preparing the probiotic sanitary products according to the production method of the sanitary products.

[0108] Example 2: A probiotic sanitary product, comprising a probiotic non-woven fabric, wherein the probiotic non-woven fabric is made of bamboo charcoal fiber, bacterial cellulose and probiotic-rich fiber prepared in Preparation Example 2 in a mass ratio of 2:1:7, and the bacterial cellulose is selected from Zhejiang Jinjiahao Green Nanomaterials, model CNF-BC.

[0109] The preparation method of the above-mentioned probiotic sanitary product comprises the following steps:

[0110] S1. Prepare probiotic non-woven fabric:

[0111] (1) 700 g of the probiotic-rich fiber prepared in Preparation Example 2 was opened, finely opened, combed, cross-laid and stretched to prepare a probiotic fiber web;

[0112] (2) preparing a bamboo charcoal fiber web by opening, fine opening, combing, cross-laying and drafting 200 g of bamboo charcoal fiber;

[0113] (3) overlapping the probiotic fiber net and the bamboo charcoal fiber net by hydroentanglement, and drying at 130° C. to obtain a base fabric;

[0114] (4) 100 g of bacterial cellulose was mixed with distilled water at a mass ratio of 1:600, and then ground at 10 bar for 10 min, at 100 bar for 20 min, and finally at 400 bar for 60 min to prepare a dispersion;

[0115] (5) adding sodium periodate to the dispersion to make the sodium periodate concentration be 0.3 mol / l, stirring at 55°C for 3 h, adding chitosan acetic acid solution with a concentration of 2 wt%, stirring at 65°C for 3 h, centrifuging, and washing with distilled water to obtain oxidized bacterial cellulose;

[0116] (6) dispersing the oxidized bacterial cellulose into a 0.5 wt% hyaluronic acid aqueous solution, ultrasonicating for 2 min at 750 W and 15 kHz to obtain a treatment solution with an oxidized bacterial cellulose concentration of 0.4 wt%, spraying the treatment solution evenly onto both sides of the base fabric, and drying at 60 ° C to obtain a non-woven fabric. The hyaluronic acid was selected from Xi'an Ruien Biotechnology, with a molecular weight of 2.1 million and a product number of Rn512;

[0117] S2. Preparation of probiotic sanitary products: using the probiotic non-woven fabric as the surface material of the sanitary products, and preparing the probiotic sanitary products according to the production method of the sanitary products.

[0118] Example 3: A probiotic sanitary product, comprising a probiotic non-woven fabric, wherein the probiotic non-woven fabric is made of bamboo charcoal fiber and bacterial cellulose prepared in Preparation Example 1 in a mass ratio of 3:2:7, and the probiotic-rich fiber is selected from Zhejiang Jinjiahao Green Nanomaterials, model CNF-BC.

[0119] The preparation method of probiotic sanitary products comprises the following steps:

[0120] S1. Prepare probiotic non-woven fabric:

[0121] (1) 700 g of the probiotic-rich fiber prepared in Preparation Example 1 was opened, finely opened, combed, cross-laid and drawn to prepare a probiotic fiber web;

[0122] (2) preparing a bamboo charcoal fiber web by opening, fine opening, combing, cross-laying and drafting 300 g of bamboo charcoal fiber;

[0123] (3) overlapping the probiotic fiber net and the bamboo charcoal fiber net by hydroentanglement, and drying at 135° C. to obtain a base fabric;

[0124] (4) 200 g of bacterial cellulose was mixed with distilled water at a mass ratio of 1:550, and then ground at 10 bar for 10 min, at 100 bar for 20 min, and finally at 400 bar for 60 min to prepare a dispersion;

[0125] (5) adding sodium periodate to the dispersion to make the sodium periodate concentration be 0.3 mol / l, stirring at 53°C for 3 h, adding chitosan acetic acid solution with a concentration of 2 wt%, stirring at 65°C for 3 h, centrifuging, and washing with distilled water to obtain oxidized bacterial cellulose;

[0126] (6) dispersing the oxidized bacterial cellulose into a 0.8 wt% hyaluronic acid aqueous solution, ultrasonicating at 750 W and 15 kHz for 2 min to obtain a treatment solution with an oxidized bacterial cellulose concentration of 0.4 wt%, spraying the treatment solution evenly onto both sides of the base fabric, and drying at 60 ° C to obtain a non-woven fabric. The hyaluronic acid was selected from Xi'an Ruien Biotechnology, with a molecular weight of 2.1 million and a product number of Rn512;

[0127] S2. Preparation of probiotic sanitary products: using the probiotic non-woven fabric as the surface material of the sanitary products, and preparing the probiotic sanitary products according to the production method of the sanitary products.

[0128] Example 4-12: A probiotic sanitary product, which is different from Example 1 in that the probiotic-rich fibers are prepared from Preparation Examples 4-12 respectively.

[0129] Example 13: A probiotic sanitary product, which is different from Example 1 in that it is made of bamboo charcoal fiber and probiotic-rich fiber prepared in Preparation Example 1 at a mass ratio of 3:7, and the specific preparation method is as follows:

[0130] (1) 700 g of the probiotic-rich fiber prepared in Preparation Example 1 was opened, finely opened, combed, cross-laid and drawn to prepare a probiotic fiber web;

[0131] (2) preparing a bamboo charcoal fiber web by opening, fine opening, combing, cross-laying and drafting 300 g of bamboo charcoal fiber;

[0132] (3) The probiotic fiber net and the bamboo charcoal fiber net are overlapped and integrated by hydroentanglement, and dried at 140° C. to obtain a nonwoven fabric.

[0133] Example 14: A probiotic sanitary product, which is different from Example 1 in that the probiotic-rich fiber prepared in Preparation Example 1 is prepared by opening, fine opening, combing, cross-lapping, drawing, hydroentanglement, and drying at 140°C.

[0134] Comparative Example

[0135] Comparative Example 1: A probiotic sanitary product, which is different from Example 1 in that the probiotic-rich fiber is made from Preparation Example 13.

[0136] Comparative Example 2: A probiotic sanitary product, which is different from Example 1 in that the probiotic-rich fiber is made from Preparation Example 14.

[0137] Comparative Example 3: A probiotic sanitary product, which is different from Example 1 in that the probiotic-rich fiber is made from Preparation Example 15.

[0138] Comparative Example 4: A probiotic sanitary product, which is different from Example 1 in that the probiotic-rich fiber is made from Preparation Example 16.

[0139] Comparative Example 5: A probiotic sanitary product, which is different from Example 1 in that the probiotic-rich fiber is made from Preparation Example 17.

[0140] Performance testing

[0141] 1. Performance test of probiotic-rich fiber: Fiber was prepared according to the method in the preparation example, and the performance test was performed according to the following method. The test results are recorded in Table 1.

[0142] 1. Number of live bacteria in the finished probiotic-rich fiber: Take 0.5 g of the finished fiber and place it in a sterile centrifuge tube. Add 4.5 mL of citric acid solution (2%, w / v). Seal the centrifuge tube with a sealing film and culture it in a constant temperature shaker at 37°C and 180 rpm for 2 hours. Dilute it with physiological saline gradiently and count the plates. Each sample has 3 replicates to test the number of colonies released from the finished fiber.

[0143] 2. Storage stability: Cut the finished fiber into a size of 10cm×10cm, culture it at 37℃ for 1-4 weeks, measure the activity of probiotics at a fixed time, and calculate the survival rate according to the following formula: Survival rate (%) = (N+1) / N×100%, where N is the number of storage weeks.

[0144] Table 1 Test results of fiber properties rich in probiotics

[0145]

[0146] Combining the data in Preparation Examples 1-3 and Table 1, it can be seen that the survival rate of probiotics in the fiber prepared by Preparation Examples 1-3 is high, reaching 8×10 8 cfu / g, and after storage at 37°C for 1 week, the survival rate can reach more than 84%. After storage for 4 weeks, the survival rate is still higher than 45%, indicating that the probiotic-rich fiber prepared by the method of the present application has a high probiotic content, stable storage performance under high temperature environment, and good activity retention rate.

[0147] Compared with Preparation Example 1, Preparation Examples 4 and 5 added a certain amount of hydroxyapatite treated with wool protein and silver ions to the electrospinning solution. It can be seen that the content of probiotics in the finished fiber increased, and the survival rate of probiotics in the fiber increased when stored at 37°C, indicating that adding treated hydroxyapatite to the electrospinning solution can improve the survival of probiotics in the fiber and increase the storage stability of probiotics.

[0148] Compared with Preparation Example 4, Preparation Example 6 did not use silver nitrate solution for impregnation during the pretreatment of hydroxyapatite. Table 1 shows that the probiotic content in the fiber prepared in Example 6 did not change much, but decreased slightly after high-temperature storage, indicating that the impregnation of silver nitrate solution had no obvious effect on improving the survival rate stability of probiotics in the fiber.

[0149] In Preparation Example 7, hydroxyapatite without added wool protein was used. Compared with Preparation Example 4, Table 1 shows that the content of probiotics in the finished fiber prepared in Preparation Example 7 decreased, and the high temperature resistance was weakened, indicating that wool protein can improve the survival of probiotics in the finished fiber and enhance the high temperature resistance effect.

[0150] Compared with Preparation Example 4, Preparation Example 8 only adds hydroxyapatite to the electrospinning solution without any treatment. It can be seen that the probiotic content in the finished fiber prepared in Example 8 decreases, and the probiotic activity is significantly weakened after high-temperature storage.

[0151] Compared with Preparation Example 4, Preparation Examples 9 and 10 further added fish oil and lactitol to the nuclear layer solution containing probiotics. As can be seen from Table 1, the amount of live bacteria in the probiotic-rich fibers prepared in Preparation Examples 9 and 10 increased significantly, the survival rate of probiotics increased, and the amount of live bacteria increased when stored at high temperatures, which also shows that the temperature resistance of probiotics in the finished fiber is improved.

[0152] Compared with Preparation Example 10, Preparation Example 11 and Preparation Example 12 did not add lactitol in Preparation Example 11, and did not add fish oil in Preparation Example 12. Through comparison of the data in Table 1, it can be seen that the number of live bacteria in the finished fiber in Preparation Example 11 and Preparation Example 12 decreased slightly, and the amount of live bacteria decreased after high-temperature storage.

[0153] Compared with Preparation Example 1, in Preparation Example 13, the probiotic embedded particles were not loaded with polyethersulfone nanofiber membrane, and the probiotic embedded particles were mixed with PE resin and additives for granulation. It can be seen that the probiotic content in the finished fiber was significantly reduced, and the high temperature storage stability of the probiotics was reduced.

[0154] In Preparation Example 14, the probiotic embedded particles were mixed with the electrospinning liquid of polyethersulfone, and the probiotic embedded particles were coated with polyethersulfone nanofibers. Compared with Preparation Example 1, the number of live bacteria in the finished fiber was reduced, but the high temperature resistance was better than that of Preparation Example 13.

[0155] Preparation Example 15 Compared with Preparation Example 1, the bacterial solution containing probiotics was added to the electrospinning solution, and soy protein, sodium alginate, etc. were not used to embed it. Table 1 shows that the number of live bacteria in the finished fiber is reduced, and the storage stability of the probiotics at high temperature is weakened.

[0156] Preparation Example 16 Compared with Preparation Example 1, the bacterial solution containing probiotics is directly mixed with PE resin for granulation. The number of live bacteria in the obtained finished fiber is significantly reduced, and the high temperature resistance effect is significantly weakened.

[0157] In Preparation Example 17, commercially available ES fibers were used, and the bacterial solution was loaded onto the ES fibers by a padding method. It can be seen that the content of live bacteria on the prepared fibers is low, and the storage stability of the probiotics is very poor.

[0158] 2. Performance test of probiotic non-woven fabric: Probiotic non-woven fabric was prepared according to the method in the embodiment and comparative example, and the performance test was carried out according to the following method, and the test results were recorded in Table 2.

[0159] 1. Breaking strength: Tested in accordance with GB / T14337-2008 "Test method for tensile properties of chemical staple fibers", the tensile speed is 5 mm / min, each sample is tested 3 times and the average value is taken.

[0160] 2. Antibacterial rate: The test was conducted in accordance with GB15979-2002 "Hygiene Standard for Disposable Sanitary Products", and the test bacteria were Staphylococcus aureus (ATCC6538), Candida albicans (ATCC10231) and Escherichia coli (8099).

[0161] 3. Water holding capacity: Cut the non-woven fabric into pieces of 2cm×2cm and conduct centrifugal test on the pieces. The centrifugal time for each time is 15min and the centrifugal force is 1500g. Each sample is tested 4 times and the average value is taken. The water holding capacity is calculated according to water holding capacity = (1-W2 / W1) × 100%, where W2 is the mass after centrifugation and W1 is the mass before centrifugation.

[0162] 4. Water vapor transmission rate: Tested in accordance with YY / T0471.2-2004 "Test methods for contact wound dressings Part 2: Water vapor transmission rate of breathable film dressings".

[0163] Table 2 Performance test of probiotic non-woven fabric

[0164]

[0165] In Examples 1-3, the probiotic-rich fibers prepared in Preparation Examples 1-3 were respectively used, and probiotic non-woven fabrics were prepared according to the methods in Examples 1-3, and probiotic sanitary products were prepared by conventional methods. It can be seen from the data in Table 2 that the probiotic non-woven fabrics obtained in Examples 1-3 have high mechanical strength, strong antibacterial properties, good water-holding performance, and can better lock in moisture and prevent evaporation.

[0166] In Example 4 and Example 5, the fibers prepared in Preparation Example 4 and Preparation Example 5 were used to prepare non-woven fabrics, respectively. It can be seen that the antibacterial rate of the fibers increased slightly, the breaking strength increased, the water holding capacity increased, and the water vapor permeability decreased, indicating that adding pretreated hydroxyapatite to the electrospinning liquid can improve the antibacterial ability, breaking strength and water holding capacity of the fibers, while reducing the water vapor permeability, reducing water evaporation, and increasing the water locking effect.

[0167] In Example 6, the fiber prepared in Preparation Example 6 was used. Compared with Example 4, no silver nitrate solution was added for impregnation during the pretreatment of hydroxyapatite. In Example 7, compared with Preparation Example 4, no wool protein was added during the pretreatment of hydroxyapatite, and the hydroxyapatite was only immersed in the silver nitrate solution. The antibacterial rate of the non-woven fabric prepared in Example 6 decreased, and the breaking strength and water-retaining effect of the non-woven fabric prepared in Example 7 decreased, indicating that pretreatment of hydroxyapatite can improve the antibacterial, moisture absorption and moisturizing effects of the fiber.

[0168] In Example 8, the fiber prepared in Preparation Example 8 was used. Compared with Example 1, the mechanical strength of the nonwoven fabric prepared in Example 8 was increased, but the antibacterial rate did not change much, and the water holding capacity and moisture retention were slightly improved. Compared with Example 4, the improvement of various properties of the nonwoven fabric prepared in Example 8 was not as good as that in Example 4.

[0169] Examples 9 and 10 respectively use the fibers prepared in Preparation Examples 9 and 10. Compared with Example 4, the mechanical properties of the nonwoven fabrics are slightly weakened, the antibacterial rate does not change much, and the water vapor permeability increases, indicating that the addition of prebiotics may increase the water permeability and breaking strength of the fibers, but the effect is not significant.

[0170] Examples 11 and 12 respectively use the fibers prepared in Preparation Examples 11 and 12. It can be seen that compared with Examples 9-10, the performances do not change much.

[0171] In Example 13, compared with Example 1, the base fabric was not treated with bacterial cellulose, and the antibacterial ability of the non-woven fabric decreased and the water holding capacity was weakened.

[0172] Example 14 Compared with Example 1, the non-woven fabric obtained by hydroentanglement of the fibers prepared in Preparation Example 1 has a decreased antibacterial rate, weakened mechanical strength, decreased water absorption capacity, and increased water vapor permeability, indicating that simply using fibers containing probiotics to prepare non-woven fabrics cannot obtain excellent antibacterial rate and other mechanical properties. The probiotic-containing fibers prepared in this application are combined with bamboo charcoal fibers and bacterial cellulose by a specific method to prepare probiotic non-woven fabrics, which can obtain better antibacterial rate, mechanical strength and water holding capacity.

[0173] In Comparative Example 1, the fiber prepared in Preparation Example 13 was used. Compared with Example 1, the probiotic non-woven fabric obtained therefrom had a decreased breaking strength and a little change in the antibacterial rate, but a decreased water holding capacity and an increased water vapor permeability.

[0174] Comparative Example 2 uses the fiber prepared in Preparation Example 14. Compared with Example 1, the probiotic-embedded particles are added to the polyethersulfone nanofiber membrane when preparing the fiber. It can be seen that the performance of the probiotic non-woven fabric is not much different from that of Example 1.

[0175] Comparative Example 3 uses the fiber prepared in Preparation Example 15. Compared with Example 1, the bacterial solution is directly added to the electrospinning solution. It can be seen that the water vapor permeability of the formed probiotic non-woven fabric is increased and the breaking strength is decreased.

[0176] Comparative Example 4 uses the fiber prepared in Preparation Example 16, in which the bacterial solution and PE resin are mixed and then melted, and the obtained probiotic non-woven fabric has significantly reduced mechanical properties and increased moisture permeability.

[0177] Comparative Example 5 uses the fiber prepared in Preparation Example 17, and Preparation Example 17 uses commercially available ES fiber. It can be seen that the mechanical properties of the probiotic non-woven fabric are reduced and the water holding capacity is weakened.

[0178] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A probiotic hygiene product, characterized in that: The invention comprises a probiotic non-woven fabric, wherein the probiotic non-woven fabric contains fibers rich in probiotics, and the fibers rich in probiotics are prepared by the following method: Sodium alginate is dissolved to prepare a solution A with a concentration of 2.5-3 wt %, polyvinyl alcohol is dissolved to prepare a solution B with a solubility of 4-5 wt %, and solution A and solution B are mixed at a mass ratio of 1:1.3-1.5 to prepare a shell solution; The bacterial solution containing probiotics is added to solution B with a concentration of 4-5wt% to prepare a nuclear layer solution, wherein the mass ratio of the bacterial solution containing probiotics to solution B is 1:20-25, and soy protein isolate and calcium chloride are mixed and dissolved in a mass ratio of 1:0.6-0.8 to prepare a receiving solution; The shell layer solution and the core layer solution are sprayed into the receiving solution by coaxial electrostatic spraying, filtered, and dried to obtain probiotic embedded particles; The polyethersulfone is dissolved to prepare an electrospinning solution with a concentration of 18-22wt%, and electrospun to prepare a polyethersulfone nanofiber membrane. Hydroxyapatite is also added to the electrospinning solution, and the mass ratio of hydroxyapatite to polyethersulfone is 0.1-0.15:

1. The hydroxyapatite is pretreated as follows: Add hydroxyapatite to the wool protein solution, mix well and then rotary evaporate, then pre-freeze at -(18-20)°C for 10-12h, vacuum dry for 70-72h, immerse in a silver nitrate solution with a concentration of 1-2g / mL, stir at room temperature in the dark for 6-7h, wash, dry and grind, the mass ratio of hydroxyapatite to wool protein solution is 1:3-5; The probiotic embedded particles are added to a pectin solution with a concentration of 5-6wt% to prepare a spray liquid, the mass ratio of the probiotic embedded particles to the pectin solution is 1:0.1-0.2, the spray liquid is evenly sprayed on the polyethersulfone nanofiber membrane in 3-7 times, dried, and crushed to prepare a blended powder, and the mass ratio of the spray liquid sprayed once to the polyethersulfone nanofiber membrane is 0.1-0.15:1; The blended powder is mixed with PE resin and additives in a mass ratio of 1:5-10:0.2-0.5, extruded and granulated to obtain a shell material, and the shell material and PET slices are composite spun, wound, bundled, stretched, heat-set, curled and cut in a mass ratio of 1-1.2:1 to obtain fibers rich in probiotics.

2. The probiotic hygiene product according to claim 1, characterized in that: Fish oil and lactitol are also added to the core layer solution, and the mass ratio of fish oil, lactitol and bacterial solution containing probiotics is 0.1-0.3:0.15-0.2:

1.

3. The probiotic hygiene product according to claim 1, characterized in that: The solvent used for dissolving the polyethersulfone is dimethylformamide and acetone in a mass ratio of 1.7:0.3-0.

5.

4. The probiotic hygiene product according to claim 1, characterized in that: The electrostatic spraying pressure is 9-10 kV, the flow rate of the shell solution is 5-7 mL / h, the flow rate of the core solution is 3-4 mL / h, and the distance between the spraying needle and the receiving liquid surface is 10-12 cm; During the electrospinning, the receiving distance is 14-15 cm, the spinning voltage is 14-15 kV, and the spinning speed is 0.04-0.06 mL / h; The temperature of the composite spinning is 285-290° C., and the cutting length is 50-51 mm.

5. The probiotic hygiene product according to claim 1, characterized in that: The probiotics are selected from at least one of Lactobacillus acidophilus, Lactobacillus bulgaricus, Lactobacillus fermentum, Lactobacillus rhamnosus, Bifidobacterium bifidum and Bifidobacterium longum.

6. The probiotic hygiene product according to claim 1, characterized in that: The probiotic non-woven fabric also contains bamboo charcoal fiber and bacterial cellulose, and the mass ratio of the bamboo charcoal fiber, the bacterial cellulose and the fiber rich in probiotics is 2-3:1-2:

7.

7. The method for preparing the probiotic sanitary product according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Preparing a probiotic non-woven fabric: opening, fine opening, combing, cross-laying and drafting the probiotic-rich fiber to obtain a probiotic fiber web; The bamboo charcoal fibers are subjected to opening, fine opening, combing, cross-laying and drafting to obtain a bamboo charcoal fiber web; The probiotic fiber net and the bamboo charcoal fiber net are overlapped into one by hydroentanglement, and dried at 130-140° C. to obtain a base fabric; The bacterial cellulose and distilled water are mixed at a mass ratio of 1:500-600, and nano-milled to obtain a dispersion, sodium periodate is added, and the mixture is stirred at 50-55° C. for 3-4 hours, and an acetic acid solution of chitosan is added, and the mixture is reacted at 60-65° C. for 2-3 hours, centrifuged, and washed to obtain oxidized bacterial cellulose, and then dispersed in a hyaluronic acid solution with a concentration of 0.5-1wt%, and ultrasonicated at 750-800W and 15-20kHz for 1.5-2min to obtain a treatment solution with an oxidized bacterial cellulose concentration of 0.4-0.5wt%, and the treatment solution is evenly sprayed on both sides of the base fabric, and dried to obtain a probiotic non-woven fabric; S2. Preparation of probiotic sanitary products: using the probiotic non-woven fabric as the surface material of the sanitary products, and preparing the probiotic sanitary products according to the production method of the sanitary products.

Citation Information

Patent Citations

  • Sanitary napkin for women

    CN110215347A

  • Colon-targeted probiotic multilayer embedded microcapsule as well as preparation method and application thereof

    CN113230280A

  • Probiotic non-woven fabric manufacturing method

    CN118932737A